PENGARUH KEGIATAN PESANTREN TERHADAP AKHLAK PESERTA DIDIK - Jamal, Moh Yusup Saepuloh; Asaroh, Dede Asri; CS, Nurhamzah (Prodi PAI IAILM Suryalaya, 2021)
This study aims to find out the influence of Islamic Boarding School Activities on the morals of students in Middle School Plus Ma'arif Al-Mushlihuun Al-Mushlihuun boarding school in Jatinagara District, Ciamis Regency. The method used in this research is descriptive method through a quantitative approach. The population taken was all students at Maarif Al-Mushlihuun Plus Middle School as many as 147. The sampling technique used was random sampling with a sample size of 22 respondents. Calculation of variables X and Y by determining the Mean value then the value is interpreted on a predetermined interpretation scale. Analysis of the data used is correlation analysis with Rank Spearman (RS). Based on the results of data processing, it is obtained that the influence of Islamic boarding school activities on the morals of students in junior high schools Plus Ma'arif Al-Mushlihuun Al-Mushlihuun boarding school has a significant positive effect on the sufficient category, it is proven that rs = 0.56 is at an interval of 0.41-0.60 and t value = 3013 ≥ t table = 1724. The activities of the pesantren determine the morals of students by 31%, the rest is influenced by other factors, which is 69%. Thus, it turns out there are still many factors that affect the morals of students.